80 Two Year Prognosis in Stable Coronary Artery Disease: A Prospective Study of 2346 Patients in UK Primary Care. (3rd June 2016) - Pope, Michael; Greenlaw, Nicola; Ford, Ian; Steg, Gabriel; Fox, Kim; Kalra, Paul
Abstract : Introduction: Coronary artery disease (CAD) is a leading cause of morbidity and mortality in the UK. Whilst data are available on outcomes for patients with acute coronary syndromes, much less is known about mortality and other cardiovascular outcomes for outpatients with stable CAD managed predominantly in primary care. CLARIFY (the "ProspeCtive observational LongitudinAl Registry oF patients with stable coronarY artery disease") is a large international study that provides a unique opportunity to describe the contemporary characteristics and outcomes for patients with stable CAD in the UK and compare them with a worldwide population. Methods: CLARIFY is an international, prospective, observational, longitudinal study designed to collect data on the characteristics, management and outcomes of patients with stable CAD. Patients were enrolled between November 2009 and June 2010 from an outpatient population with a history of at least one of the following: myocardial infarction (MI), coronary artery bypass grafting (CABG), or percutaneous coronary intervention (PCI) >3 months prior to recruitment; coronary stenosis. >50%; or reversible myocardial ischemia. Enrollment occurred across 45 countries. To reduce selection bias, each participating physician recruited 10–15 consecutive outpatients with CAD to meet a predefined country target of 25 patients per million inhabitants (range 12.5–50). In the UK, patients were recruited from 250 GP surgeries, selected to provide a geographic and socioeconomic profile representative of the population. Baseline data included demographics, clinical history, risk factors and drug therapy. Patients are followed up for 5 years with annual assessments to assess clinical status, outcomes and medications and 6-monthly telephone calls An independent centre, the Robertson Centre for Biostatistics at the University of Glasgow, was responsible for data collection and analysis. Results: 32, 901 patients were recruited worldwide, of which 2, 346 were from the UK and form this study population. Table 1 outlines the baseline characteristics as compared to the rest of the CLARIFY population. Mean age was 67 ± 9 years in the UK (rest of CLARIFY 63.9 ± 10.5, p < 0.001) and around ¾ were male. Significant co-morbidities were common, together with a high prevalence of cardiovascular risk factors (18% with diabetes and 70% with a history of smoking in the UK). Although MI was more common there was a significantly lower prevalence of heart failure in the UK cohort. At 2 year follow-up all cause mortality was 3% and cardiovascular mortality 1.3%. Conclusions: In a large, representative cohort of stable CAD patients in primary care within the UK 2-year mortality is 3% and is similar to that seen in the rest of the international CLARIFY population. Secondary prevention appears to be reasonable although there may be room for improvement. Although there appear to be differences in rates of MI and stroke, further analysis is needed to explore the possible causes for these.